2011
DOI: 10.1016/j.tsf.2010.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of thin films of mixed Ni–W oxide made by reactive DC magnetron sputtering

Abstract: This is an author produced version of a paper published in Thin Solid Films. This paper has been peer-reviewed but does not include the final publisher proofcorrections or journal pagination. AbstractThin films of Ni x W 1-x oxides with x = 0.05, 0.19, 0.43 and 0.90 were studied. Films with thicknesses in the range 125 -250 nm were deposited on silicon wafers at room temperature by reactive DC magnetron co-sputtering from targets of Ni and W. The films were characterized with X-ray diffraction (XRD), scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The thicknesses of the films and their dielectric functions have been extracted from experimental data using a parametric model as well as a pbp fit. The obtained dielectric functions are in good agreement with the earlier published IR spectra of 3WO 3 ·H 2 O [3,4,7,12] and the presence of ½WO 3 ·H 2 O compounds in the films is indicated. Moreover, it was proved that films retain a great amount of water, especially the film with a thickness of 2127 nm.…”
Section: Discussionsupporting
confidence: 89%
“…The thicknesses of the films and their dielectric functions have been extracted from experimental data using a parametric model as well as a pbp fit. The obtained dielectric functions are in good agreement with the earlier published IR spectra of 3WO 3 ·H 2 O [3,4,7,12] and the presence of ½WO 3 ·H 2 O compounds in the films is indicated. Moreover, it was proved that films retain a great amount of water, especially the film with a thickness of 2127 nm.…”
Section: Discussionsupporting
confidence: 89%
“…Film thicknesses lay between 124 and 304 nm, with thickness non-uniformities around 4%. 16 We obtained results on Figs. 3 and 4. It should be noted that some correlations appear between the parameters of the Gaussian oscillators, which implies that the solutions are not unique and there exist multiple sets of Gaussians which provide the same dielectric functions.…”
Section: B Datamentioning
confidence: 98%
“…18 A detailed description of the parametric model used to represent the Ni x W 1Àx oxide films is given elsewhere. 16 …”
Section: Thin Films: Preparation and Surface Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Researches on metal doping have been performed on Nb, [20] Mo, [17] Ni, [46,47] Ti, [48] Ru, [49] V, [50] Ce, [51] and Sn, [52] and the results have shown that WO 3 with metal doping can have superior properties in one way or another. [10] Researches on metal doping have been performed on Nb, [20] Mo, [17] Ni, [46,47] Ti, [48] Ru, [49] V, [50] Ce, [51] and Sn, [52] and the results have shown that WO 3 with metal doping can have superior properties in one way or another.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%